Exploration of Teachers' Perception of The Influence of Positive and Negative Emotions in Learning Interactions At Vocational High School - Siti Ussa' Diyah; Zulfajri; Raoda Tul Jannah Maruddani Maruddani; Mardiana (Journal of Innovative and Creativity, 2025)
Teacher emotions play a crucial role in classroom interactions, particularly in shaping the learning environment, motivating students, and enhancing instructional effectiveness. This study aims to explore teachers' perceptions of the influence of positive and negative emotions in classroom interactions at SMKN 3 Kota Jambi. A qualitative research method was employed, using observation, interviews, and data analysis with two teachers as samples. The findings indicate that positive emotions, such as a friendly demeanor, encouraging tone, and praise, significantly enhance students' motivation and engagement in learning. Conversely, negative emotions, such as frustration and a raised voice, tend to create tension in the classroom and reduce student participation. Teachers who effectively manage their emotions using self-reflection, peer-sharing, and relaxation techniques exhibit more productive classroom interactions. Therefore, school support through teacher welfare programs is essential in helping educators manage stress and improve instructional quality.